Analysis of Chromium, Nickel, Zinc, and Manganese in Wastewater Matrices Using ICP-OES at PT Medialab Indonesia - Fahrevi, Ganang Adha; Salmahaminati (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Industrial wastewater from metal-related industries commonly contains heavy metals such as chromium (Cr), manganese (Mn), nickel (Ni), and zinc (Zn), which pose significant risks to aquatic ecosystems and human health if discharged without adequate treatment. This study aimed to determine total metal concentrations in inlet (untreated) and outlet (treated) wastewater matrices using Inductively Coupled Plasma–Optical Emission Spectroscopy (ICP-OES) at PT Medialab Indonesia, Cikarang Barat, and to evaluate the efficiency of the wastewater treatment process in accordance with Peraturan Menteri Lingkungan Hidup No. 5 Tahun 2014, specifically Appendix 47. Wastewater samples were subjected to acid digestion using HNO₃ and HCl prior to ICP-OES analysis. Quality assurance and quality control (QA/QC) parameters including calibration linearity (R²), percent relative percent difference (%RPD), and percent recovery (%REC) were rigorously evaluated. All calibration curves exhibited excellent linearity with R² values of 0.9996–0.9998. Analytical precision was confirmed with %RPD values ranging from 0.66% to 6.42%, and matrix spike recoveries fell within the acceptable range of 87.91%–98.62%. Total metal concentrations in the inlet were 0.0218 mg/L (Cr), 0.1354 mg/L (Mn), 0.0486 mg/L (Ni), and 0.8233 mg/L (Zn). Following the treatment, removal efficiencies of 84.2% for Cr, 93.7% for Mn, and 87.2% for Zn were achieved. All outlet concentrations complied fully with applicable regulatory limits, confirming that the ICP-OES method supported by rigorous QA/QC procedures is reliable and effective for total metal monitoring in complex industrial wastewater matrices.